Implications of converting native forest areas to agricultural systems on the dynamics of CO2 emission and carbon stock in a Cerrado soil, Brazil - Silva, Bruna de Oliveira [UNESP]; Moitinho, Mara Regina [UNESP]; Panosso, Alan Rodrigo [UNESP]; Oliveira, Dener Marcio da Silva; Montanari, Rafael [UNESP]; Moraes, Mario Luiz Teixeira de [UNESP]; Milori, Débora Marcondes Bastos Pereira; Bicalho, Elton da Silva [UNESP]; La Scala, Newton [UNESP] (Elsevier, 2024)
The conversion of native vegetation to agricultural areas leads to a natural process of carbon loss but these systems can stabilize in terms of carbon dynamics depending on the management and conversion time, presenting potential to both store and stabilize this carbon in the soil, resulting in lower soil respiration rates. In this context, this study aimed to investigate the effect of converting native Cerrado forest areas to agricultural systems with a forest planted with Eucalyptus camaldulensis and silvopastoral systems on the dynamics of CO2 emission and carbon stock at different soil depths. The experimental sites are located in the Midwest of Brazil, in the coordinates 20°22′31″ S and 51°24′12″ W. Were evaluated soil CO2 emission (FCO2), soil organic carbon, the degree of humification of soil organic matter (HLIFS), soil temperature, soil moisture, and soil chemical and physical attributes. The soil of the area is classified as an Oxisol (Haplic Acrustox). Soil samples were collected at depths of 0.00–0.10, 0.10–0.20, 0.20–0.30, and 0.30–0.40 m. The lowest FCO2 values were found in the silvopastoral system (1.05 μmol m−2 s−1), followed by the native forest (1.65 μmol m−2 s−1) and the eucalyptus system (1.96 μmol m−2 s−1), indicating a 36% reduction in FCO2 compared to the conversion of the native forest to the silvopastoral system and an increase of 19% when converting the native forest to the eucalyptus system. The soil chemical attributes (N, K+, Ca2+, H++Al3+, CEC, and organic carbon) showed a decrease along the profile. The shallowest depths (0.00–0.10 and 0.10–0.20 m) presented no differences between systems but the subsequent depths (0.20–0.30 and 0.30–0.40 m) had a difference (95% confidence interval), relative to N, Ca2+, H++Al3, CEC, and organic carbon stock (OCS), and the soil under silvopastoral system showed a higher concentration of these attributes than the native forest. The multivariate analysis showed that the eucalyptus and silvopastoral systems did not differ from the forest in the shallowest soil layer but differed from each other. This behavior changed from the second assessed depth (0.10–0.20 m), in which the silvopastoral system stands out, differing both from the eucalyptus system and from the native forest, and this behavior is maintained at the following depths (0.20–0.30 and 0.30–0.40 m). OCS, H++Al3, CEC, and nitrogen are strongly related to land use change for silvopastoral system. Regarding the behavior/relationship of attributes as a function of depth, the silvopastoral system contributed to soil carbon accumulation and stability over consecutive years.
Keywords: Climate change; Silvopastoral system; Soil respiration; Sustainability